Modern Corner Bookshelf Inspired By ASPAM Building - Chia Zhen, Lee; Abdul Halip, Juliana (Research in Management of Technology and Business, 2020)
Most of the people stayed in small houses always faced the problems less enough storage for books or magazines but normal bookshelf occupied more space. Therefore, the objectives of this study are to identify the design characteristics of corner bookshelf, to design and to develop a prototype of corner bookshelf inspired by ASPAM building for small houses. A total of 50 respondents who live in Batu Pahat were asked by the given questionnaire. Data obtained from the survey was applied for sketches, design survey, mock up, technical drawing and fabrication of the prototype. Findings revealed that people prefer a corner bookshelf with 3 tiers, open shelf, equipped with door, made from the plywood and has neutral colour. A total of 45 thumbnails, 8 ideations, and 4 idea developments were sketched and the final design was determined by the design survey. A prototype of corner bookshelf made from plywood and finished with Formica in the oak pattern was successfully fabricated. The modern corner bookshelf could benefit family those stay in small houses for storing books and magazines.